Designing and executing a checklist for evaluating midwifery students' practical skills - Mansoureh Refaei; Hassan Ahmadini; Seyedeh-Zahra Masoumi; Arezoo Shayan (Iranian Journal of Nursing and Midwifery Research, 2020)
Background: This study aimed to design and execute a reliable checklist for evaluating midwifery students' clinical skills. Materials and Methods: In this cross-sectional study, 8 checklists were designed and validated for midwifery procedures. The students' performances were compared using this method and two other evaluation methods. Results: The face and content validity of all questions were approved (content validity ratio and content validity index> 0.80, inter-rater reliability> 0.50, and Cronbach's alpha> 0.70). The rate of the students' satisfaction was 19%, 14%, and 76% with the nonchecklist method, the general checklist, and the designed checklist, respectively. Furthermore, both students (F2,60= 107.07, p < 0.004) and evaluators (F2,9 =152.23, p < 0.001) gained significantly higher attitude scores towards the new checklist compared to the two other methods. Conclusions: The designed checklist was quite reliable and valid for evaluating the midwifery students' clinical skills.